RANCANG BANGUN MESIN PENCACAH SAMPAH PLASTIK - Dian Anisa Rokhmah Wati; Agung Samudra (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2022)
The purpose of this study was to determine the performance of the plastic waste chopping machine. The type of research used is experimental research. The object of research is a plastic waste chopping machine by modifying the shape to be simpler. Plastic waste shredder can work well. This machine can chop plastic with a thickness of 0.3 mm in 14.4 kg/hour and plastic waste with a thickness of 0.5 mm in a time of 18 kg/hour.